The effect of self-concept in the sense of accomplishment before performing a task in a kindergarten classroom - Vaquero Ibarra, Susana (Pulso. Revista de educación, 2015)
This paper presents an experimental study that has followed the methodology of action research, based on systematic observation, and that tries to assess the positive impact of self-concept in the teaching-learning process of Infant Education children. Educational research and psychology applied to education has demonstrated the relationship between cognition and emotion and its impact on the teaching-learning process. This study was conducted with a group of second-year Infant Education children composed of 18 4-year-old pupils. The group was subjected to a test during a four-week period before and after having carried out a model of educational intervention focused on the development of selfconcept. The results supported our hypothesis: educational intervention focused on the development of self-concept has a positive impact on improving the pupils´ sense of self-accomplishment.
Keywords: Self-esteem; Attitude; Learning; Self-concept; Stimulus